2000
DOI: 10.1111/j.1600-0684.2000.290606.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the menstrual cycle, pregnancy and early lactation on haematology and plasma biochemistry in the baboon (Papio hamadryas)

Abstract: The changes in the haematology and clinical biochemistry associated with the different stages of the menstrual cycle, gestation and lactation in the baboon (Papio hamadryas) were evaluated in a prospective longitudinal study. Serial EDTA and heparin blood samples were collected from 12 baboons. Haemoglobin concentration, haematorcrit, red blood cell and white blood cell counts were decreased in the luteal compared to the follicular phase (P<0.001); the reverse effect was observed for platelet count, total prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
22
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 9 publications
8
22
0
1
Order By: Relevance
“…It is not only relevant for diagnosing disorders of the hematologic system but also is important indices of animal health and production (Oladele et al 2005). Several factors affect cellular and plasma haemodynamics such as breed (Tibbo et al 2008), pregnancy (Farooq et al 2011) and lactation (Harewood et al 2000). The results of this study demonstrated that the total red cell count was influenced only by the reproductive stages (P<0.0001) and was not affected by breed (P>0.4718) or interaction between the factors (Table 3).…”
Section: Resultssupporting
confidence: 47%
“…It is not only relevant for diagnosing disorders of the hematologic system but also is important indices of animal health and production (Oladele et al 2005). Several factors affect cellular and plasma haemodynamics such as breed (Tibbo et al 2008), pregnancy (Farooq et al 2011) and lactation (Harewood et al 2000). The results of this study demonstrated that the total red cell count was influenced only by the reproductive stages (P<0.0001) and was not affected by breed (P>0.4718) or interaction between the factors (Table 3).…”
Section: Resultssupporting
confidence: 47%
“…Several other studies showed no significant changes in Hb Concentration and RBC Count during various phases of menstrual cycle 10 . There was a pronounced tendency towards an increase in Hb and RBC Count from the early menstrual phase until the postovulatory period, with a subsequent decrease towards the end of the cycle 11,12 . The cyclic variations act as indicators of iron status and are a potential source of error when iron status is assessed in large population surveys that include women of reproductive age 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Also in the study, the lowest TLC was recorded during pregnancy, while the highest was obtained during dioestrus. Harewood et al (2000) observed a decrease in Hb, PCV and RBC, but an increase in MCV during pregnancy. By contrast, significant higher PCV was recorded in pregnant West African Dwarf ewes than either the lactating or dry ewes (Durotoye and Oyewale, 2000).…”
Section: Reproductive Cycle Variation In Haematologic Parameters Varimentioning
confidence: 93%
“…Various workers have reported changes in haematological parameters during the different phases of the oestrous cycle (Harewood et al, 2000;Alavi-Shoushtari et al, 2006;Chaudhari and Mshelia, 2006). Significantly higher erythrocyte and leucocyte counts have been reported in oestrus in comparison with the dioestrus phase in cattle (Soliman and Zaki, 1963;Hussain and Daniel, 1991).…”
Section: Reproductive Cycle Variation In Haematologic Parameters Varimentioning
confidence: 99%
See 1 more Smart Citation